(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The theme of this Study presents analysis and discuss to the "Share the framework for assessing inflation," a practical study in a sample of joint stock companies listed on the Iraq Stock Exchange for the years (2009-2013). To determine the extent of the disparity between the nominal value of shares (Nominal Value) before deducting inflation and the real value (Real Value) per share, after deducting inflation in the case of zero growth. The study relied on annual reports of the companies of the research sample of the Iraq Stock Exchange, as well as the Iraqi Securities Commission. Besides the annual reports issued by the Ministry of Planning, as well as annual reports and statistical bulletin issued by the Central Bank of Iraq. It is framed theoretical framework on the subject of evaluation of the stock of the companies, and inflation. Either In the analysis of applied research approach was used in the analytical value of the stock to extract the cost of financing the property using the nominal capitalism asset pricing model (CAPM), while used to measure the cost of financing real property Fisher equation (Fisher) which is extracted through which the value of the stock From which is extracted by using the value of the stock dividend discount model. The study concluded a set of conclusions which, inflation leads to increased risk of systemic work because the companies use the property financing in financing their projects. Results of the analysis also showed a decline in the real cost of financing by large than it was the nominal cost of funding. This shows that inflation large role in the disparity true for the nominal cost of funding. The value of shares fell because of the low cost of financing (which is the basis in the calculation of the share price) as a result of excluding the impact of inflation, which was contrary to the hypothesis Search. The study also concluded a number of recommendations, including the need for more attention to companies new financial disclosure and the addition of important indicators that benefit researchers as well as investors and not just only by showing only the basic operations. Inflation rates, and the lack of financial statements with an extension demonstrates effect of inflation. Need to focus on the diversification of forms of funding and show the cost of each form of financing in the financial statements for researchers and investors, because of the importance of the cost of financing in the real value of the stock account.